Validation of a new patient-reported outcome measure of balance recovery confidence (BRC) for community-dwelling older adults: a study protocol. (22nd October 2021) - Soh, Shawn Leng-Hsien; Lane, Judith; Gleeson, Nigel; Xu, Tianma; Bte Abdul Rahman, Fahria; Yeh, Ting-Ting; Soon, Benjamin; Tan, Chee-Wee
Abstract: Background: Patient-reported outcome measures (PROMs) provide clinicians a greater understanding of patients' perceived ability in their physical performance. Existing PROMs on falls efficacy provide meaningful information about the perceived ability in older people to perform common activities of daily living without falling. However, the perceived ability to recover balance from a slip, a trip, or volitional movements has been inadequately assessed. Balance recovery confidence relates to the judgment of self-reactive ability. The scale of balance recovery confidence (BRC) is a new PROM that measures perceived balance recovery self-efficacy. The purpose of the study protocol is to describe the first psychometric evaluation of BRC's measurement properties. Objective: This study is a validation phase of a newly developed PROM conducted in Singapore. Methods: Two hundred community-dwelling older adults, aged 65 years and older, will complete five self-reported instruments (BRC, Activities-specific Balance Confidence Scale, Falls Efficacy Scale-International, Late-Life Function and Disability Instrument-Function and Global Perceived Effect) and three performance measures (Hand strength dynamometer, 30-second Chair Stand, Mini BESTest). Classical test theory methods will assess acceptability, data completeness, targeting of the items, scaling assumptions, internal consistency reliability and construct validity. Factor analysis will establish unidimensionality. Rasch analysis will evaluate item fit, differential item functioning, response scale ordering, targeting of persons and items and the reliability. Results: The findings from this study will be published in peer-reviewed journals and presented at national and international conferences in rehabilitation-specific context. Conclusions: This is the first validation study of BRC. The study will give confidence among clinicians and researchers to use the BRC in fall management research and clinical practice.